(untitled) (Acta Judicial Journal, 2018)
The technological revolution of communications has ended up reaching the Administration of Justice, colliding with its structures. New problems solved by court resolutions, have arisen regarding electronic communications between courts and the rest of legal practitioners intervening in the process, due to its compulsory nature. In this paper we try to analyze, from a practical point of view, some of these problems in the field of labour jurisdiction, according to the Code of Civil Procedure, of which it is subsidiary.